Metafísica dos atos livres - Alves, Alda Maria Soares Abreu (2019)
Metaphysics of Free Acts establishes a close dialogue between philosophy and dance. A "writing of the self" that encompasses both the analytical and conceptual dimension as well as the poetic and aesthetic dimension of thought, bringing to light expressive acts that stem from the desire to return the craft of art to its true sources: the pure metaphysical activity. Eros is an intensive operator of the devices of this Metaphysics of Acts, which in rethinking our currently practices of subjectivation, redesings notions such as Individual, Subject, and Self, and proposes new ways to experience body, time and sexuality. The premises that guide the metaphysics proposed by Antonin Artaud in his Theater of Cruelty are the same that, throughout this process, danced thoughts and memories of sleeping courage in the hollows of the body and in the hollows of thought. The reason of this research-creation is ultimately to close the gap between thinking and acting, to witness the forces that reside between what already is and what is yet to be born, it has no name or form yet, but it thinks and acts in a way, whole and free in us. To what extent do we possess and enjoy the germinating forces that inhabit all the relationships, connections, and cuts that make up our bodies so that we can actually access the true revolutions?